Assessment of chemomechanical removal of carious lesions using Papacarie Duo ™: Randomized longitudinal clinical trial - Simone Ferreira Borges Matsumoto; Lara Jansiski Motta; Thays Almeida Alfaya; Carolina Cardoso Guedes; Kristianne Porta Santos Fernandes; Sandra Kalil Bussadori (Wolters Kluwer Medknow Publications, 2013)
Background: Chemomechanical removal of carious lesions consists of the dissolution of carious tissue by the application of a natural or synthetic agent, followed by atraumatic mechanical removal. Aim: The aim of the present study was to assess the effectiveness of Papacarie Duo ® gel in the chemomechanical removal of carious lesions in primary teeth in comparison to the traditional method (low-speed bur). Settings and Design: A randomized clinical trial was conducted with 20 children between 5 and 8 years of age. Materials and Methods: Two teeth were treated in each child (split-mouth design), with the randomization of two methods: Group 1 - chemomechanical caries removal with Papacarie Duo™; and Group 2 - removal of carious dentin tissue using a low-speed bur. Both methods involved restoration with glass ionomer cement and follow up. The following aspects were evaluated: time required for the procedure; pain (face evaluation scale); rtention of the restorative material in the cavity; and the presence of secondary caries after 30 days. Statistical Analysis Used: Chi-squared test, Student's t-test, and Wilcoxon test. Results: No statistically significant differences between methods were found regarding time required for the procedure (P = 0.13), the occurrence of pain (P = 0.585), or restoration status at the 30-day clinical evaluation (P = 0.713). Conclusion: The findings of the present study demonstrate that the two methods achieve similar results. The advantages of minimally invasive treatment, such as chemomechanical caries removal with Papacarie Duo™, are its ease of use, patient comfort, and the fact that it causes less damage to dental tissue.